Proceedings of the 1st International Conference on Education Social Sciences and Humanities (ICESSHum 2019) 2019
DOI: 10.2991/icesshum-19.2019.65
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Unity of Students’ Writing on Background of the Study of Research Proposal

Abstract: This study aims to find out the coherence and unity of students' writing on background of the study of research proposals, the problems faced and the causes of difficulties encountered. The type of this research was descriptive research. The source of data was the background of the study and the instruments used were documents and interview. The finding shows that most of the students' writing had coherence and unity. Nevertheless, they still faced a number of problems. The problems in coherence were no repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The finding of this study is similar to the research finding from RahmtAllah since he saw the result of his analysis is most of the students applied the pronouns in their writing [12]. Furthermore, Dasril, Zaim, and Ningsih analyzed the students' coherence in the background of the problem of the thesis proposal [13]. Then, they found that most of the students had built coherence in their writing.…”
Section: Total 24supporting
confidence: 84%
“…The finding of this study is similar to the research finding from RahmtAllah since he saw the result of his analysis is most of the students applied the pronouns in their writing [12]. Furthermore, Dasril, Zaim, and Ningsih analyzed the students' coherence in the background of the problem of the thesis proposal [13]. Then, they found that most of the students had built coherence in their writing.…”
Section: Total 24supporting
confidence: 84%
“…From the point of content, the assessment is based on the intrinsic element of a paragraph. It should be unity and coherence (Dasril et al, 2019). Unity refers to the idea that becomes the focus of the one-whole paragraph.…”
mentioning
confidence: 99%